Correlation Between Noise Exposure Intensity, Length of Employment, and Hearing Loss Among Fishermen - Anderias Umbu Roga; Ishak Israel Muda; Delvisari Dedu Ngara (Knowledge and Environmental Science for Living and Global Health, 2026)
Occupational noise exposure remains a major health risk among fishermen, particularly those operating motorized boats. This study aims to analyze the correlation between noise exposure intensity, length of employment, and hearing loss among fishermen in Pesisir Selatan Regency, West Sumatra, Indonesia. A cross-sectional quantitative design was applied involving 60 fishermen selected through purposive sampling. Noise intensity was measured using a sound level meter, while hearing loss was assessed using audiometric examination. Length of employment was obtained through structured interviews. Data were analyzed using Pearson correlation and multiple regression tests. The results showed that the average noise exposure exceeded the permissible limit of 85 dB. There was a significant positive correlation between noise intensity and hearing loss (r = .62; p < .01), as well as between length of employment and hearing loss (r = .58; p < .01). Simultaneously, both variables significantly influenced hearing impairment among fishermen (p < .001). These findings indicate that prolonged exposure to high-intensity noise increases the risk of Noise-Induced Hearing Loss (NIHL). The study suggests the need for occupational health interventions, including the use of hearing protection devices and routine health monitoring. In conclusion, noise exposure and working duration are important determinants of hearing loss among fishermen and should be addressed in policy and practice.